2017
DOI: 10.4330/wjc.v9.i12.813
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of epicardial stenosis in patients with microvascular disease using pressure drop coefficient: A pilot outcome study

Abstract: AIMTo investigate the patient-outcomes of newly developed pressure drop coefficient (CDP) in diagnosing epicardial stenosis (ES) in the presence of concomitant microvascular disease (MVD).METHODSPatients from our clinical trial were divided into two subgroups with: (1) cut-off of coronary flow reserve (CFR) < 2.0; and (2) diabetes. First, correlations were performed for both subgroups between CDP and hyperemic microvascular resistance (HMR), a diagnostic parameter for assessing the severity of MVD. Linear regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The results were similar for a FFR cutoff of 0.80 and associated CDP cutoff of 25.4. The MVD sub-group analysis (Hebbar et al, 2017) for %MACE and survival analysis showed similar trends in favor of CDP for both CFR < 2.0 and diabetic sub-groups. Both of these sub-groups were correlated with possible MVD in literature (Feigl, 1983;Muller et al, 1996;Miura et al, 2003;Bagi et al, 2004;Pijls et al, 2007;Picchi et al, 2010;Johnson et al, 2012).…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…The results were similar for a FFR cutoff of 0.80 and associated CDP cutoff of 25.4. The MVD sub-group analysis (Hebbar et al, 2017) for %MACE and survival analysis showed similar trends in favor of CDP for both CFR < 2.0 and diabetic sub-groups. Both of these sub-groups were correlated with possible MVD in literature (Feigl, 1983;Muller et al, 1996;Miura et al, 2003;Bagi et al, 2004;Pijls et al, 2007;Picchi et al, 2010;Johnson et al, 2012).…”
Section: Introductionmentioning
confidence: 70%
“…where P = P a -P d is the pressure drop across the stenosis, P a and P d are the mean pressures measured proximal and distal to the stenosis at hyperemia, respectively, and the distal dynamic pressure is the product of blood density (ρ) and the square of the average peak flow velocity (APV) distal to the stenosis at hyperemia at a constant value of 0.5. The ρ was assumed to be a constant (1.05 g/cm 3 ), as it does not change significantly during the hyperemic (high shear) condition (Banerjee et al, 2009;Effat et al, 2016;Hebbar et al, 2017). Therefore, CDP represents the ratio between the total pressure drop (viscous loss plus loss due to momentum change with pressure recovery) and the dynamic pressure during blood flow.…”
Section: Cdp Formulationmentioning
confidence: 99%
See 3 more Smart Citations